Adsorption and Desorption of Copper by Calcareous Arid Soils - Joshi, D C (Annals of Arid Zone, 2016)
The study on adsorption of copper by calcareous arid soils of Rajasthan, India, showed that with increasing additions of copper from 2 to 500 mg Cu L-1 there was slight increase in the equilibrium concentration values in Khajwan, Panchroli, Pali (0.114 to 0.285 mg L-1) and in Asop I and Asop II (0.859 to 3.33 mg L-1) soils.The amount of copper adsorbed at 2mg L-1 (0.01 to 0.019 mg g-1) increased to 4.99 mg g'l at 500 mg Cu L-1 addition, Adsorption of copprr followed the Freundlich's equation. The same concentration of desorbed copper (1.79x10-6 to 1.35x10-5 moles L-1 low concentration of desorbed copperÂ· (2.69x10-6 to 2.19x1O-5 moles L-1) at 500 mg Cu L-1 and the copper hydroxide potential values in the range of 185 to 19.9 indicated precipitation of added copper rather than multi layer adsorption.